Fidelity of muscle fibre reinnervation modulates ageing muscle impact in elderly women. (21st August 2019) - Sonjak, Vita; Jacob, Kathryn; Morais, José A.; Rivera‐Zengotita, Marie; Spendiff, Sally; Spake, Carole; Taivassalo, Tanja; Chevalier, Stéphanie; Hepple, Russell T.
Abstract : Key points: Susceptibility to age‐related muscle atrophy relates to the degree of muscle denervation and the capacity of successful reinnervation. However, the specific role of denervation as a determinant of the severity of muscle aging between populations with low versus high physical function has not been addressed. We show that prefrail/frail elderly women exhibited marked features of muscle denervation, whereas world class octogenarian female master athletes showed attenuated indices of denervation and greater reinnervation capacity. These findings suggest that the difference in age‐related muscle impact between low‐ and high‐functioning elderly women is the robustness of the response to denervation of myofibers. Abstract: Ageing muscle degeneration is a key contributor to physical frailty; however, the factors responsible for exacerbated vs . muted ageing muscle impact are largely unknown. Based upon evidence that susceptibility to neurogenic impact is an important determinant of the severity of ageing muscle degeneration, we aimed to determine the presence and extent of denervation in pre‐frail/frail elderly (FE, 77.9 ± 6.2 years) women compared to young physically inactive (YI, 24.0 ± 3.5 years) females, and contrast these findings to high‐functioning world class octogenarian female masters athletes (MA, 80.9 ± 6.6 years). Muscle biopsies from vastus lateralis muscle were obtained from all three groups to assess denervation‐related morphological and transcriptional markers. The FE group displayed marked grouping of slow fibres, accumulation of very small myofibres, a severe reduction in type IIa/I size ratio, highly variable inter‐subject accumulation of neural cell adhesion molecule (NCAM)‐positive myofibres, and an accumulation of pyknotic nuclei, indicative of recurring cycles of denervation/reinnervation and persistent denervation. The MA group exhibited a smaller decline in type IIa/I size ratio and fewer pyknotic nuclei, accompanied by a higher degree of type I fibre grouping and larger fibre group size, suggesting a greater reinnervation of denervated fibres. Consistent with this interpretation, MA had higher mRNA levels of the reinnervation‐promoting cytokine fibroblast growth factor binding protein 1 (FGFBP1) than FE. Our results indicate that the muscle of FE women has significant neurogenic atrophy, whereas MA muscle exhibit superior reinnervation capacity, suggesting that the difference in age‐related muscle impact between low‐ and high‐functioning elderly women is the robustness of the response to denervation of myofibres. Key points: Susceptibility to age‐related muscle atrophy relates to the degree of muscle denervation and the capacity of successful reinnervation. However, the specific role of denervation as a determinant of the severity of muscle aging between populations with low versus high physical function has not been addressed. We show that prefrail/frail elderly women exhibited marked features of muscle denervation, whereas world class octogenarian female master athletes showed attenuated indices of denervation and greater reinnervation capacity. These findings suggest that the difference in age‐related muscle impact between low‐ and high‐functioning elderly women is the robustness of the response to denervation of myofibers.